2018
DOI: 10.2147/cmar.s163432
|View full text |Cite
|
Sign up to set email alerts
|

Distinct prognostic values of mRNA expression of glutathione peroxidases in non–small cell lung cancer

Abstract: IntroductionGlutathione peroxidases (GPxs) constitutes an enzyme family which has the ability to reduce free hydrogen peroxide to water and lipid hydroperoxides to their corresponding alcohols, and its main biological roles are to protect organisms from oxidative stress-induced damage. GPxs include eight members in different tissues of the body, and they play essential roles in carcinogenesis. However, the prognostic value of individual GPx in non-small cell lung cancer (NSCLC) remains elusive.Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…Previous researches have reported the oncogenic role of GPX1 in several carcinomas. For example, Liu et al demonstrated that glutathione peroxidases have distinct prognostic values for non-small cell lung carcinoma [ 24 ]. Chen et al indicated that GPX1 promotes NSCLC cisplatin-resistance via ROS-induced PI3K/AKT pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have reported the oncogenic role of GPX1 in several carcinomas. For example, Liu et al demonstrated that glutathione peroxidases have distinct prognostic values for non-small cell lung carcinoma [ 24 ]. Chen et al indicated that GPX1 promotes NSCLC cisplatin-resistance via ROS-induced PI3K/AKT pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in some types of cancer GPx1 is upregulated, e.g., adult acute leukemia, thyroid tumors or urothelial carcinoma, whereas other types showing a downregulation such as adult chronic leukemia, breast cancer cell lines, gliomas or renal cell carcinoma [ 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, it has also been reported that especially the upregulation of GPx in cancer tissues results in poor prognosis in tumor diseases such as kidney cancer, large cell and non-small cell lung carcinoma, squamous cell carcinoma or prostate cancer [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-associated mortality worldwide in men and women, and its prognosis remains dismal with a five-year survival rate of <15% (1). Non-small cell lung cancer (NSCLC), including lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), accounts for ~75–80% of all lung cancer cases (2). In addition, although there are several treatment methods for patients with early-stage NSCLC, including surgery, chemotherapy, radiotherapy and molecular targeted therapy, the number of NSCLC cases is still increasing.…”
Section: Introductionmentioning
confidence: 99%